P130 Increase in global DNA methylation at 3 months of methotrexate use is not associated to response in early ra patients. (21st February 2018) - Gosselt, HR; Rotte, MC de; Hazes, JM; de Jonge, R; Heil, SG
Abstract : Introduction: Methotrexate (MTX) is a first-line therapy in early Rheumatoid Arthritis (eRA). However, up to 40% of treated patients do not adequately respond to MTX. MTX interferes with the folate cycle, where it indirectly inhibits the global DNA methylation donor S-adenosylmethionine (SAM). Thus, we hypothesised that global DNA methylation changes during MTX use are associated with treatment response. Objectives: To examine whether there is a change in global DNA methylation (Δ%Meth) upon MTX use and if this change is associated to MTX response (ΔDAS28) in eRA patients. Methods: DNA was isolated from whole blood (n=120) and Peripheral Blood Mononuclear Cells (PBMCs, n=83) of eRA patients, before and 3 months after MTX use. Samples were collected from the Treatment in the Rotterdam Early Arthritis Cohort (tREACH), a multicenter, stratified single-blind clinical trial of eRA patients. Selected patients received triple (MTX +SSZ + HCQ) or monotherapy (MTX) combined with corticosteroids. 7 CpG sites within Long-Interspersed Nuclear Elements (LINE-1), a proxy for global DNA methylation, were quantified by Sequenom Epityper. Paired t-tests or Wilcoxon Signed Rank tests were conducted to assess a change in methylation. ΔDAS28 score over 3 months was used as a measure for response. Associations between ΔDAS28 and Δ%Meth were corrected for baseline DAS28 in a linear regression model. Results: In leukocytes, %Meth did not significantly change over time. However, in PBMCs%Meth in CpG1 (ΔMeth=2.61%, p=0.008), CpG2 (ΔMeth=0.73%, p=0.039) and CpG11.12 (ΔMeth=0.56%, p=0.016) significantly increased over 3 months of MTX use after Bonferroni correction. Δ%Meth in CpG8.9 was significantly associated to the ΔDAS28 (B=0.29, p=0.039), yet this was no longer significant after Bonferroni correction. Δ%Meth was not significantly associated to ΔDAS28 in any of the other LINE1 CpG sites tested. Conclusions: PBMC global DNA methylation in LINE-1 CpG sites increased upon 3 months of MTX use. However, this change in methylation is not associated to MTX response. Further research is needed to investigate the role of global DNA methylation in these patients. Disclosure of interest: None declared